Current management of acute type B dissection in 2021. (January 2023) - Matsuda, Hitoshi
The rationale for thoracic endovascular aortic repair (TEVAR) for type B aortic dissection depends on the phase of disease: acute phase, which is 'complicated', subacute to early chronic phase, which requires 'preemptive TEVAR' and chronic phase, which entails 'prevention of further dilatation and rupture'. Low operative mortality and morbidity after TEVAR for complicated acute type B aortic dissection have been reported with significant improvement during midterm survival. 'Retrograde' type A dissection, which can be described as type B0, X (X>3) according to a new reporting standard, has reportedly been treated with TEVAR with less invasiveness. TEVAR is the first and possibly the only effective strategy for acute type B dissection, so that expansion of indications for type B0, X, as described in the new reporting standard has been validated.